Fear and loathing in Las Vegas [videorecording (DVD)] - Gilliam, Terry; Davies, Tod, 1955-; Cox, Alex, 1954-; Grisoni, Tony; Depp, Johnny; Toro, Benicio del, 1967-; Pecorini, Nicola, 1957-; Thompson, Hunter S. (Universal Studios Home Entertainment, 2011)
Fueled by a suitcase full of pharmaceuticals, journalist Raoul Duke and his sidekick Dr. Gonzo set off on a fast and furious ride through nonstop neon, surreal surroundings and a crew of crazy characters.